Prognostic significance of volume-based 18F-FDG PET/CT parameter in patients with surgically resected non-small cell lung cancer - Lee, J. Y.; Choi, J. Y.; Heo, J. H.; Han, J.; Jang, S. J.; Kim, K.; Kim, J.; Shim, Y. M.; Kim, B.-T. (Nuklearmedizin - NuclearMedicine, 2016)
Aim: We investigated the prognostic value of volume-based 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET) parameters compared with other factors including several immunohistochemical biomarkers in patients with surgically resected non-small cell lung cancer (NSCLC). Patients, methods: Study participants: 290 patients with surgically resected and histopathologically confirmed NSCLC. The maxmum standardized uptake value (SUVmax) and metabolic tumour volume (MTV) of the primary tumour were obtained on 18F-FDG PET/ computed tomography (CT) for initial staging and Ki-67 labeling index (LI), p16, CD31 and cyclin E were evaluated in the primary tumours by immunohistochemical staining. Survival analyses for variables including PET parameters, immunohistochemical biomarker and other clinical factors were performed using the Kaplan-Meier method and Cox proportional hazards regression analysis. Results: In univariate analyses, tumour stage, tumour size, and MTV were significant prognostic factors for decreased overall survival (OS) and disease-free survival (DFS). Multivariate analyses showed MTV and tumour stage were significant predictors of poor OS (MTV, hazard ratio (HR) = 1.135, p = 0.015; stage, HR = 0.644, p = 0.025) and DFS (MTV, HR = 1.128, p = 0.043; stage, HR = 0.541, p = 0.009). Conclusion: The MTV of primary tumours is a significant prognostic factor for survival along with tumour stage in patients with surgically resected NSCLC. The MTV can predict OS and DFS better than immuno histochemical biomarkers.
Keywords: 18F-FDG; PET/CT; lung cancer; metabolic tumour volume; immunohistochemical biomarkers